Recent Development of Net Neutrality Conditions in Japan: Impact of Fiber Wholesale and Long-term Evolution (LTE) - Toshiya Jitsuzumi (International Telecommunications Society (ITS), 2015)
The Japanese broadband market was very competitive until recently owing to the interconnection rules and the significant market power (SMP) regulations on the incumbent fixed telecom giant, NTT East/West. Japan's regulator, the Ministry of Internal Affairs and Communications (MIC), could let the market dynamism deal with the net neutrality issue without introducing any “special” rules. However, technological developments in mobile broadband have turned mobile operators into leading players in the broadband ecosystem, which is making the broadband access market increasingly oligopolistic. The fiber wholesale recently introduced by NTT East/West may accelerate this trend by realizing the virtual integration of NTT Docomo and NTT East/West. Since mobile network operators are less disciplined in Japan's telecom framework than fixed ones are, the MIC cannot sit back and do nothing. This paper compares two of the tools the MIC may use—increasing competitive pressure in the market and controlling the behavior of dominant mobile operators—and concludes that the latter is more promising. The author recommends that the MIC begin examining the re-regulation of mobile operators and the introduction of new rules for net neutrality.
Keywords: 330